2017
DOI: 10.1007/978-3-319-66923-6_65
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Organizational Culture on Performance Measurement System Design, Implementation and Use: Evidence from Moroccan SMEs

Abstract: Several earlier studies have viewed organizational culture (OC) as a key factor for performance measurement systems (PMS), yet its role is not well understood and the reviewed literature indicates a gap in articles describing the relationship between various types of OC and PMS. Thus, the following study sets out to explore how OC type impacts PMS design, implementation and use. The investigation is carried out using the case study methodology in two Moroccan manufacturing SMEs. Our findings suggest that there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…However, for SPM to function correctly at Higher Education Institutions, it must be modified. Some studies [6] offer a unique perspective on (SPM) practice in Higher Education Institutions. Traditional approaches (SPM), for example, are not suitable for Higher Education Institutions, according to a survey [15], [18].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for SPM to function correctly at Higher Education Institutions, it must be modified. Some studies [6] offer a unique perspective on (SPM) practice in Higher Education Institutions. Traditional approaches (SPM), for example, are not suitable for Higher Education Institutions, according to a survey [15], [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Following that, strategic costing, strategic planning, control systems, and strategic performance assessment systems [5] were discussed. This is remarkable given that educational reforms began at the close of the twentieth century, and the old management of higher education has become obsolete [6]. Experiential research on (SPM) and performance has taken a contingency approach, with researchers searching for systematic links between certain (SPM) aspects and Improving performance in Higher Education [7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Jardioui et al (2017) found in their research that companies with a flexible culture tend to use a more balanced set of performance measures and PMM to meet learning goals, improving and implementing strategy. On the other hand, companies with a culture of control use PMM for monitoring and legitimization, mostly based on financial measures.…”
Section: Performance-driven Culture Characteristicsmentioning
confidence: 99%
“…We can assume that companies that pay enough attention and energy to a performance-driven corporate culture will have a more developed PMM. To date, there are very little empirical data that would explicitly confirm the relationship between the PMM system and corporate culture (Jardioui et al 2017;Smith and Bititci 2017). The paper aims to fill this research gap and empirically examine the relationship between these two factors.…”
Section: Introductionmentioning
confidence: 99%
“…Organizations that commit adequate time and resources to build a performance-driven company culture and implement a well-designed performance management system can be expected to succeed. There is abundant research evidence that directly verifies the relationship between organizational control systems and corporate culture [30]. There are several findings where researchers measured employee performance in companies through several tools, including setting measurable OKRs (Objectives and key results) and individual goals, implementing a project or task management tool, tracking training competition, benchmarking performance by implementing sprints, performing a skill gap analysis, and building employee performance metrics individually.…”
Section: Introductionmentioning
confidence: 99%